Lead-acid battery separator and lead-acid battery

The lead-acid battery separator with a controlled water-soluble organic solvent and inorganic material laminate addresses charge acceptance and cycle life issues by enhancing ion permeability and reducing resistance, ensuring better battery performance under partial state of charge conditions.

JP2025000344APending Publication Date: 2025-01-07ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023100149
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing lead-acid batteries face issues with charge acceptance and cycle life deterioration due to the formation of highly crystalline sulfate on the electrode surface during partial state of charge (PSoC), leading to increased internal resistance and reduced performance.

Method used

A lead-acid battery separator with a laminate containing an inorganic material and a controlled amount of water-soluble organic solvent, which enhances ion permeability and reduces internal resistance, improving charge acceptance and cycle life.

Benefits of technology

The separator provides low internal resistance and improved charge acceptance, maintaining battery performance under PSoC conditions, thereby extending the cycle life of lead-acid batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025000344000001_ABST
    Figure 2025000344000001_ABST
Patent Text Reader

Abstract

To provide a separator for a lead-acid battery having excellent ion permeability, and a lead-acid battery using the same having excellent charge acceptance or cycle life.SOLUTION: A separator for a lead-acid battery includes a substrate and a laminate provided on at least one surface of the substrate, the laminate includes an inorganic material, and a water-soluble organic solvent is contained in the laminate and the substrate, and the content of the water-soluble organic solvent is greater than 0 mass% and not more than 0.3 mass% on the basis of the total mass of the separator for a lead-acid battery.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a separator for a lead-acid battery and a lead-acid battery using the same. [Background technology]

[0002] Lead-acid batteries are widely used worldwide in in-vehicle applications, such as passenger cars, buses, trucks, motorcycles, golf carts, etc., and in industrial applications, such as forklifts, farm machinery, railways, uninterruptible power supplies (UPS), and communication devices, etc. In particular, in recent in-vehicle applications, there is a demand for battery performance that can support operation at a partial state of charge (PSoC) of approximately 50% to 90%, such as hybrid electric vehicles (HEVs) and idling start-stop (ISS) vehicles.

[0003] The main performance requirements for lead-acid batteries are charge acceptance, cycle characteristics, and water loss characteristics. Lead-acid batteries equipped with charge control or regenerative charging functions for environmental performance and fuel efficiency improvement have limited opportunities to charge. Therefore, charge acceptance is required to efficiently charge a large amount of energy into the battery. If a battery is maintained in PSoC for a long time, the cycle characteristics are likely to decrease. The reason is that in PSoC batteries, highly crystalline sulfates are easily formed on the electrode surface, and if the formed sulfate crystals accumulate, the charge acceptance of the electrode is dramatically reduced (sulfation), eventually leading to the end of the battery life. In addition, when the negative electrode reaches the hydrogen generation potential, water is decomposed and water loss occurs. Therefore, from the viewpoint of maintainability, improvement and maintenance of water loss characteristics are required.

[0004] Lead-acid battery separators are generally membranes with a microporous structure that have voltage resistance characteristics, and are placed in close contact with the surfaces of both electrodes to prevent short circuits between the positive and negative electrodes. It is expected that the performance of batteries can be improved by improving the separator structure and controlling the electrode surface reaction that occurs at the contact surface between the separator and the electrode.

[0005] Patent Document 1 discloses a technique for improving the charge acceptance of a lead-acid battery by using a separator for the lead-acid battery coated with a carbon material. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2015 / 171595 Summary of the Invention [Problem to be solved by the invention]

[0007] However, Patent Document 1 does not clarify what type of coating layer or separator structure having a coating layer is best from the viewpoint of improving charge acceptance.

[0008] The present disclosure has been made in consideration of the above circumstances, and has an object to provide a separator for a lead-acid battery having excellent ion permeability, and a lead-acid battery using the same having excellent charge acceptance or cycle life. [Means for solving the problem]

[0009] The above problems are solved by the following technical means. [1] A separator for a lead-acid battery comprising a substrate and a laminate provided on at least one surface of the substrate, the laminate including an inorganic material, and a water-soluble organic solvent contained in the laminate and the substrate, A separator for a lead-acid battery, wherein the content of the water-soluble organic solvent is greater than 0 mass % and not more than 0.3 mass % based on the total mass of the separator for a lead-acid battery. [2] 2. The separator for a lead-acid battery according to item 1, wherein the water-soluble organic solvent has a boiling point of 200° C. or lower. [3] 3. The lead-acid battery separator according to item 1 or 2, wherein the water-soluble organic solvent has a vapor pressure of 0.04 kPa or more at 20° C. [4] 4. The separator for a lead-acid battery according to any one of items 1 to 3, wherein the inorganic material is made of a carbon material. [5] 5. The lead acid battery separator according to item 4, wherein the carbon material comprises furnace black, acetylene black, ketjen black, or a combination thereof. [6] A lead-acid battery comprising a battery case, a positive electrode, a negative electrode, and dilute sulfuric acid, the lead-acid battery having the separator according to any one of items 1 to 5 disposed between the positive electrode and the negative electrode. [7] 7. The lead acid battery according to item 6, wherein the laminate is disposed in contact with the negative electrode. Effect of the Invention

[0010] According to the present invention, it is possible to provide a separator for a lead-acid battery having excellent ion permeability, and by using the separator, it is possible to provide a lead-acid battery having low internal resistance, good charge acceptance, and good cycle life characteristics under PSoC. [Brief description of the drawings]

[0011] [Figure 1] 1 is a correlation graph between the amount of water-soluble organic solvent in a lead-acid battery separator and the ER ratio. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present disclosure (hereinafter, abbreviated as "the present embodiment") will be described in detail. Note that the present disclosure is not limited to the following embodiment, and can be modified in various ways within the scope of the gist of the present disclosure.

[0013] <Lead-acid battery separator> The separator for a lead-acid battery (hereinafter, also simply referred to as "separator") of this embodiment has a substrate and a laminate placed on at least one side of the substrate, and the laminate contains an inorganic material. The separator contains a water-soluble organic solvent in the substrate and the laminate, and the content of the water-soluble organic solvent is greater than 0 mass% and 0.3 mass% or less based on the total mass of the separator. The separator of this embodiment is disposed between a positive electrode and a negative electrode, and suppresses or prevents electrical short-circuiting between the positive electrode and the negative electrode. The laminate may be laminated on both sides of the substrate, and may be laminated entirely or partially on one or both sides of the substrate. In this embodiment, when the laminate is "placed" on one or both sides of the substrate, this includes the case where the laminate is directly placed on the substrate and the case where the laminate is indirectly placed via another layer. The separator is usually microporous so that ions can pass through. The maximum pore size of the separator is preferably 500 nm or less, 400 nm or less, 300 nm or less, 200 nm or less, or 150 nm or less. The lower limit of the maximum pore size that can be combined with these upper limits is, but is not limited to, for example, 10 nm or more, 30 nm or more, or 50 nm or more.

[0014] <Water-soluble organic solvent> In this embodiment, when the separator contains a water-soluble organic solvent, the water-soluble organic solvent can improve the ion permeability inside the separator and reduce the internal resistance of the lead-acid battery, thereby improving the cycle characteristics and charge acceptance performance of the lead-acid battery. Without being bound by theory, the presence of a trace amount of water-soluble organic solvent on the microporous surface of the separator introduces a moderate amount of hydrophilic functional groups, which facilitates the movement of ions such as sulfate ions and protons via water molecules, thereby reducing the internal resistance and improving the charge acceptance. More specifically, when comparing the electrical resistance (ER), which is an index of ion permeability, between a separator containing more than 0% water-soluble organic solvent and a separator containing 0% water-soluble organic solvent, the separator containing more than 0% water-soluble organic solvent has a lower ER value, indicating better ion permeability. From this viewpoint, the content of the water-soluble organic solvent is preferably 0.001 mass% or more, 0.005 mass% or more, 0.01 mass% or more, 0.03 mass% or more, 0.05 mass% or more, 0.08 mass% or more, or 0.1 mass% or more, based on the total mass of the separator.

[0015] In this embodiment, when the separator contains an excessive amount of the water-soluble organic solvent, the water-soluble organic solvent may deteriorate the ion permeability inside the separator and increase the internal resistance of the lead-acid battery, which may reduce the performance of the lead-acid battery. Without being bound by theory, the presence of an excessive amount of the water-soluble organic solvent on the microporous surface of the separator causes electrical repulsion between the water-soluble organic solvent and sulfate ions or protons, inhibiting the movement of ions, thereby increasing the internal resistance and reducing the charge acceptance. More specifically, when the ER of a separator containing more than 0.3% of the water-soluble organic solvent is compared with that of a separator containing 0% of the water-soluble organic solvent, the separator containing more than 0.3% of the water-soluble organic solvent has a larger ER value and shows poorer ion permeability. From this viewpoint, the content of the water-soluble organic solvent is preferably 0.3% by mass or less, 0.28% by mass or less, 0.26% by mass or less, 0.24% by mass or less, 0.22% by mass or less, or 0.20% by mass or less based on the total mass of the separator.

[0016] Water-soluble organic solvents may be oxidized and degenerated into carboxylic acids or organic acids having a carboxyl group due to the influence of the electrolyte, which is mainly composed of sulfuric acid, and the charge / discharge reactions during the manufacture and practical use of lead-acid batteries. It is known that carboxylic acids or organic acids having a carboxyl group corrode lead electrodes inside lead-acid batteries. Without being bound by theory, it is believed that when the separator contains an excess of water-soluble organic solvent, the carboxylic acids or organic acids having a carboxyl group produced by oxidation corrode the electrodes, thereby reducing the charge / discharge capacity, charge acceptance, and cycle life.

[0017] The content of water-soluble organic solvents in the separator can be measured using Agilent 6890 (Agilent Technologies) and JEOL Automass SUN (JEOL Ltd.) as GC / MS equipment, and DB-1 (0.25mm id x 30m) (25μm liquid layer thickness) (Agilent Technologies). As an example of analysis, each sample is shredded, about 0.3g is immersed in 2ml of chloroform for 20 hours, and the extract is directly measured by GC / MS. A chloroform solution of water-soluble organic solvents with known concentrations is prepared as a standard, and measured under the same conditions as the sample, to create a calibration curve. The amount of water-soluble organic solvent in the sample can be quantified from the obtained calibration curve.

[0018] The method of the water-soluble organic solvent in the separator is not limited, but the water-soluble organic solvent in the form of gas, liquid or solid may be directly introduced into the separator, or may be indirectly introduced into the separator during the manufacture of the separator or the formation of the laminate. In order to prevent the content of the water-soluble organic solvent from becoming excessive during the introduction, a water-soluble organic solvent with a low boiling point that is easy to remove after introduction is preferable, and the boiling point of the water-soluble organic solvent is preferably 207°C or less, or 204°C or less, more preferably 200°C or less, 190°C or less, 180°C or less, 170°C or less, 160°C or less, or 150°C or less. The lower limit of the boiling point of the water-soluble organic solvent is not particularly limited, and may be arbitrarily combined with the upper limit of the boiling point, for example, more than 0°C, 20°C or more, 35°C or more, etc.

[0019] From the same viewpoint as the boiling point, the water-soluble organic solvent in the separator is preferably a water-soluble organic solvent having a high vapor pressure at 20° C., which is easy to remove after introduction. The vapor pressure of the water-soluble organic solvent at 20° C. is preferably 5.69×10 -5 Pa or more, or 3.30 x 10 -2 Pa or more, more preferably 4.70×10 -2 The upper limit of the vapor pressure of the water-soluble organic solvent at 20° C. is not particularly limited and may be arbitrarily combined with the lower limit, and may be, for example, 1 kPa or less.

[0020] From the viewpoint of preventing the content of the water-soluble organic solvent from becoming excessive, it is preferable that both of the boiling point and the vapor pressure at 20°C of the water-soluble organic solvent in the separator satisfy the numerical ranges, but the effect can be obtained by satisfying at least one of the conditions of the boiling point or the vapor pressure at 20°C.

[0021] Examples of the water-soluble organic solvent that satisfies the above conditions of boiling point and vapor pressure at 20° C. include alcohols, ethers, esters, carbonates, carboxylic acids, glycols and glycol ethers, ketones, nitriles, phenols, and other aprotic solvents. More specifically, for example, 1-butanol, 2-butanol, 1-propanol, 2-propanol, tert-butyl alcohol, ethanol, methanol, diethylene glycol dimethyl ether, 1,4-dioxane, tetrahydrofuran, diisopropyl ether, diethyl ether, γ-valerolactone, γ-butyrolactone, butyl acetate, propyl acetate, ethyl acetate, methyl acetate, diethyl carbonate, ethyl methyl carbonate, dimethyl carbonate, normal butyric acid, propionic acid, acetic acid, dipropylene glycol monomethyl ether, ethylene glycol monotertiary butyl ether, ethylene glycol mono normal butyl ether, and dipropylene glycol. Examples of the dimethyl ether include dimethyl ether, 3-methoxy-3-methyl-1-butanol, propylene glycol monobutyl ether, ethylene glycol monoisopropyl ether, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether, propylene glycol monomethyl ether, ethylene glycol dimethyl ether, diisobutyl ketone, cyclohexanone, methyl isobutyl ketone, methyl ethyl ketone, acetone, benzonitrile, propionitrile, acetonitrile, ortho-cresol, phenol, dimethyl sulfoxide, N,N-dimethylacetamide, and N,N-dimethylformamide, and these may be used alone or in combination of two or more.

[0022] (Laminate) Without being bound by theory, the laminate in this embodiment functions as a retention layer for the electrolyte inside the lead-acid battery, facilitating diffusion of sulfate ions inside the layer, and suppressing high concentration of sulfate ions near the electrode, thereby improving charge acceptance from the viewpoint of chemical equilibrium. The laminate according to this embodiment includes an inorganic material. The laminate can be adjusted, for example, by changing the materials such as the substrate, laminate, resin, surfactant, thickener, thickness of the laminate, and formation conditions of the laminate.

[0023] The thickness of the laminate according to this embodiment is preferably 0.1 to 300 μm, 0.1 to 200 μm, 0.1 to 100 μm, 0.1 to 50 μm, 0.1 to 25 μm, or 0.1 to 15 μm, from the viewpoint of preventing peeling or falling off of the laminate from the separator and forming a uniform laminate on the substrate surface.

[0024] <Main material of laminate> The main material forming the laminate may be an inorganic material, an organic material, or a mixture of an organic material and an inorganic material. The main material forming the laminate is a material that occupies 50 mass% or more, preferably 70 mass% or more, more preferably 80 mass% or more, and even more preferably 90 mass% or more, based on the total mass of the laminate. Examples of inorganic materials include ceramic materials such as alumina (Al2O3), zirconia (ZrO2), silicon nitride (Si3N4), and silicon carbide (SiC), silica (SiO2), and carbon materials consisting only of carbon atoms (C).

[0025] From the viewpoint of electrical conductivity, the laminate in this embodiment preferably contains a carbon material or is preferably made of a carbon material. Examples of carbon materials include carbon clusters such as graphite, activated carbon, carbon black, graphene, and fullerene, carbon monolithic materials, and mixtures thereof. Among the above carbon materials, from the viewpoint of reducing surface resistance, at least one selected from the group consisting of furnace black, acetylene black, ketjen black, graphite, and carbon nanotubes is preferable, and at least one selected from the group consisting of furnace black, acetylene black, and ketjen black is more preferable. Without being bound by theory, the surface electrical resistance value of the laminate is 10 Ω or more, which makes it effective as an auxiliary conductive path. That is, the current flows preferentially to the electrode rather than the laminate, thereby maintaining the function of the battery as a whole. On the other hand, the separator according to this embodiment can combine excellent cycle characteristics, charge acceptance performance (DCA), and unit water reduction amount (liquid reduction characteristic) when using a lead-acid battery by suppressing the surface resistance value of the laminate to 10,000 Ω or less.

[0026] The median particle size (d50) of the main material forming the laminate is preferably 0.01 μm to 50 μm, more preferably 0.01 μm to 30 μm, and even more preferably 0.01 μm to 10 μm, from the viewpoint of facilitating the formation of a uniform layer thickness.

[0027] <Surfactants> The laminate according to the present embodiment preferably contains a surfactant from the viewpoint of uniformly dispersing the main material of the laminate. When the main material of the laminate is a carbon material, the surfactant allows the carbon material to be uniformly distributed throughout the laminate, forming a uniform conductive path, so that it is more preferable that the laminate contains a surfactant. As the surfactant, various surfactants can be used, such as anionic surfactants such as sulfate ester type, phosphate ester type, carboxylic acid type, and sulfonic acid type; cationic surfactants such as quaternary ammonium salt type and amidoamine type; amphoteric surfactants such as alkyl betaine type, amido betaine type, and amine oxide type; nonionic surfactants such as ether type, fatty acid ester type, and alkyl glucoxide; and polymeric surfactants such as polyacrylic acid, polyacrylic acid salts, polysulfonate salts, polynaphthalene sulfonate salts, polyalkylene polyamine alkylene oxide, polyalkylene polyimine alkylene oxide, polyvinyl pyrrolidone, and cellulose type. In order to prevent the fillers from agglomerating together, these can be used alone or in combination of two or more types. The surfactant is not limited to these, so long as it has the effect of uniformly dispersing the main material of the laminate. The laminate preferably contains, as the surfactant, at least one selected from the group consisting of ionic surfactants, i.e., anionic surfactants, cationic surfactants, and amphoteric surfactants.

[0028] The amount of the surfactant is preferably 1 part by mass to 100 parts by mass, and more preferably 10 parts by mass to 60 parts by mass, based on 100 parts by mass of the total of the main materials of the laminate.

[0029] <resin> The laminate according to the present embodiment preferably contains a resin from the viewpoint of increasing the binding property of the main material and suppressing peeling or falling off of the laminate from the substrate. Examples of the resin include styrene-based resins, acrylic resins, acrylic-urethane-based resins, acrylic-styrene-based resins, vinyl acetate-acrylic resins, styrene-butadiene-based resins, acrylonitrile-butadiene-based resins, natural rubber-based resins, polybutadiene-based resins (BR resins), methyl methacrylate-butadiene-based resins, 2-vinylpyridine-styrene-butadiene-based resins (VP ​​resins), chloroprene resins (CR resins), polyolefin-based resins such as polyethylene, polypropylene, polybutene, ethylene / propylene / butene copolymers, and mixtures thereof; modified polyolefin-based resins obtained by chlorinating or acid-modifying such polyolefin-based resins; fluorine-containing resins such as polyvinylidene fluoride or polytetrafluoroethylene; fluorine-containing rubber binders such as vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymers and ethylene-tetrafluoroethylene copolymers; (meth)acrylic acid-styrene-butadiene copolymer resins and hydrogenated products thereof; polyvinyl alcohol resins; and polyvinyl alcohol-polyacetate copolymer resins.

[0030] Among the above resins, from the viewpoint of improving the binding property and heat resistance of the separator, acrylic resin or styrene resin is more preferable, and acrylic resin is further preferable. In this specification, "acrylic resin" includes acrylic copolymer resins, such as acrylic-urethane resins, acrylic-styrene resins, acrylic-styrene-butadiene resins, and vinyl acetate-acrylic resins, as well as polymers such as acrylic resins. In this embodiment, the acrylic copolymer is preferably used in the form of a latex from the viewpoint of the binding property and heat resistance of the separator, and the latex may be a dispersion of acrylic copolymer particles in an aqueous solvent or an aqueous solvent (a mixture of water and an organic solvent). In this specification, "styrene resin" includes styrene copolymer resins, such as acrylic-styrene resins, styrene-butadiene resins, acrylic-styrene-butadiene resins, and 2-vinylpyridine-styrene-butadiene resins, as well as polymers such as styrene resins.

[0031] The amount of the resin is preferably 1 to 200 parts by mass, 10 to 100 parts by mass, or 30 to 70 parts by mass, relative to 100 parts by mass of the total of the main materials of the laminate.

[0032] These resins may contain one or more other components in the above-mentioned composition. The resin according to the present embodiment is not limited to one type, and multiple types can be used in combination within the range in which the effects of the present invention can be obtained. For example, a combination of an acrylic resin and a styrene resin can be exemplified.

[0033] <Thickener> The laminate according to the present embodiment preferably contains a thickener from the viewpoint of suppressing peeling or falling off of the laminate from the substrate and forming a uniform laminate on the substrate surface. Examples of the thickener include synthetic polymers such as polyethylene glycol, polypropylene glycol, urethane-modified polyether, polyacrylic acid (excluding the case where it is used as the above-mentioned "acrylic resin"), polyvinyl alcohol, and vinyl methyl ether-maleic anhydride copolymer, cellulose derivatives such as carboxymethyl cellulose (CMC), carbomethoxy cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose, natural polysaccharides such as xanthan gum, diutan gum, welan gum, gellan gum, guar gum, carrageenan gum, and pectin, and starches such as dextrin and pregelatinized starch. The thickener is appropriately selected from the viewpoints of the viscosity, pot life, and particle size distribution of the slurry. These can be used alone or in combination of two or more.

[0034] The amount of the thickener is preferably 0.1 to 50 parts by mass, and more preferably 1 to 20 parts by mass, relative to 100 parts by mass of the total of the main materials of the laminate.

[0035] <Combination of surfactant, resin and thickener> In this embodiment, from the viewpoint of suppressing peeling or falling off of the laminate from the substrate and forming a laminate uniformly on the substrate surface, the laminate preferably contains at least two selected from the group consisting of the surfactant, resin, and thickener described above in addition to the main material, and more preferably contains at least two selected from the group consisting of an ionic surfactant, an acrylic copolymer resin, and a thickener. When the laminate contains two or three of the surfactant, resin, and thickener, the contents of each of them may be as described above.

[0036] <Base material> The substrate is not particularly limited as long as it is microporous so that ions can pass through it, and preferably includes porous membranes made from natural or synthetic materials such as thermoplastic polymers such as polyvinyl and polyolefin, thermosetting polymers such as phenolic resin, rubber materials such as natural or synthetic rubber and latex, fibrous materials such as synthetic wood pulp (SWP), glass fiber, synthetic fiber, and cellulose fiber, and combinations thereof, and more preferably, microporous membranes made from thermoplastic polymers. Thermoplastic polymers basically include any acid-resistant thermoplastic material suitable for use in lead-acid batteries, and preferred thermoplastic polymers include, for example, polyvinyl and polyolefin. Polyvinyl includes, for example, polyvinyl chloride (PVC). Polyolefin includes, for example, polyethylene and polypropylene. Polyethylene includes, for example, ultra-high molecular weight polyethylene (UHMWPE).

[0037] 《Lead acid battery》 The lead acid battery of this embodiment includes the separator for lead acid batteries of this embodiment. The lead acid battery is a lead acid battery in which a positive electrode, a negative electrode, and a separator according to this embodiment are disposed between the positive electrode and the negative electrode. An electrolyte containing dilute sulfuric acid can be used as the electrolyte. The positive electrode grid constituting the positive electrode may be lead or a lead alloy, and the positive electrode active material may be lead oxide, for example, lead dioxide. The negative electrode grid constituting the negative electrode may be lead or a lead alloy, and the negative electrode active material may be lead, and the lead negative electrode itself may be, for example, in a spongy form. In addition, the active materials of these positive and negative electrodes may contain 50 mass % or less of other metal elements other than lead or lead alloy. The dilute sulfuric acid is sulfuric acid having a specific gravity of 1.1 to 1.4, and the electrolyte may contain an additive. The additive may contain, for example, aluminum ions from the viewpoint of suppressing sulfation. Other additives include metal ions such as lithium ions and sodium ions.

[0038] By providing the separator according to this embodiment between the positive electrode and the negative electrode, a lead-acid battery having low internal resistance, good charge acceptance, and good cycle life characteristics under PSoC can be obtained. From the viewpoint of efficiently reducing and decomposing lead sulfate on the surface of the negative electrode during charging, it is preferable that the separator laminate described above is disposed in contact with the negative electrode. The separator for a lead-acid battery according to this embodiment can be used in both an open-type lead-acid battery and a valve-regulated lead-acid battery.

[0039] <<Manufacturing method for lead-acid battery separator>> <Preparation of substrate> Hereinafter, the manufacturing method will be described using an example of a substrate made of polyolefin, for example, ultra-high molecular weight polyethylene. However, the substrate is not limited to substrates obtained by the manufacturing method described below, as long as the laminate of the present embodiment can be formed thereon.

[0040] The method for producing the substrate includes the following steps: providing a thermoplastic polymer, such as ultra-high molecular weight polyethylene (hereinafter "UHMWPE"); Providing a particulate filler; Providing a processing plasticizer that is liquid at room temperature (25°C); mixing the UHMWPE, a particulate filler, and a processing plasticizer to form a mixture; extruding the mixture through a die, such as a slot die or a blown film die, to form a sheet; an extraction step to partially or completely remove the plasticizer from the sheet, thereby forming a microporous matrix; After the sheet-forming step, the sheet may be further processed by casting onto chill rollers, calendering, or blowing prior to the extraction step. The cast, calendered, or otherwise processed sheet may then be subjected to the extraction step described above to partially or completely remove the plasticizer, thereby forming a microporous matrix.

[0041] The microporous matrix obtained by the above method includes UHMWPE, plasticizer (if partially extracted), and particulate filler dispersed throughout the matrix. The particulate filler preferably accounts for 5 to 95 percent by weight of the microporous matrix. In the present specification, the term "microporous matrix" refers to a structure having a network of interconnected pores, the entire microporous matrix being connected by the above-mentioned constituent materials. The pores preferably account for 25 to 90 percent of the volume of the microporous matrix. The method for producing a substrate may further include, after the extraction step, a step of stretching the microporous matrix; and a step of calendering the stretched microporous matrix to produce a final microporous material. By carrying out the above-mentioned calendering, a substrate having excellent dimensional stability even at high temperatures can be formed.

[0042] Formation of Laminate The laminate according to the present embodiment may be directly laminated on the surface of a substrate, or may be indirectly laminated as a laminate of a substrate having a laminate structure consisting of a single layer or multiple layers. In the latter case, the laminate according to the present embodiment may be introduced as the final step of a process of laminating a single layer or multiple layers onto the substrate, or the laminate may be introduced into a part of the laminate material, and then the substrate and the laminate member including the laminate according to the present embodiment may be superimposed and introduced.

[0043] The method for forming a laminate to be laminated to a substrate includes the following steps: mixing the materials that will form the laminate with a solvent; introducing a mixture of materials onto a surface of a substrate or laminate; drying the mixture to remove the solvent; The material is preferably homogenized in a solvent to form a mixture. The solvent may be an aqueous solvent or an organic solvent, and from the viewpoint of improving ion permeability and reducing the internal resistance of the lead-acid battery, it is preferable to use a slurry containing the water-soluble organic solvent described above. The method of introduction includes applying the mixture in a wet state to the surface of the substrate or laminate, for example, by using a die coating method or a gravure coating method. The substrate or laminate to which the mixture has been applied may be further processed, such as by pressing. The step of drying the mixture to remove the solvent is preferable from the viewpoint of adjusting the content of the water-soluble organic solvent in the separator.

[0044] <<Manufacturing method of lead-acid battery>> A lead-acid battery including the separator of the present disclosure can be manufactured by placing each component in a battery container so that the separator of the present disclosure is disposed between a lead oxide positive electrode and a lead negative electrode, and injecting dilute sulfuric acid as an electrolyte. From the viewpoint of efficiently reducing and decomposing lead sulfate on the surface of the negative electrode during charging, it is preferable to make the layer face to face and contact the negative electrode, or to orient the layer in a state of contact with the negative electrode. The form of the separator for a lead-acid battery can be determined so as to be compatible with each component of the lead-acid battery. The positive electrode grid constituting the positive electrode may be lead or a lead alloy, and the positive electrode active material may be lead oxide, for example, lead dioxide. The negative electrode grid constituting the negative electrode may be lead or a lead alloy, the negative electrode active material may be lead, and the lead negative electrode itself may be, for example, in a spongy form. In addition, the active materials of these positive and negative electrodes may contain other metal elements in the above composition at 30 mass% or less. In addition, in the manufacturing method of a lead-acid battery, the electrolyte may further contain an additive as a source of metal ions such as aluminum ions, lithium ions, and sodium ions.

[0045] A lead acid battery including the separator of the present disclosure can be manufactured by placing each component in a battery container such that a substrate is provided between a lead oxide positive electrode and a lead negative electrode, and a layer is disposed between the substrate and the lead negative electrode, and then injecting dilute sulfuric acid as an electrolyte. The layer may be disposed on either the substrate surface or the negative electrode surface. The method described above in "Formation of a laminate" can be used as a method for disposing the layer on the substrate surface.

[0046] The method of disposing the layer on the surface of the negative electrode includes the following steps: mixing the material forming the layer with a solvent; introducing the mixture of materials to the surface of the negative electrode; and drying the mixture to remove the solvent. In disposing on the surface of the negative electrode, the material forming the layer may be the layer-constituting material described above for this embodiment, and is preferably homogenized in a solvent to form a mixture. The solvent may be an aqueous solvent or an organic solvent. The method of introduction includes applying the mixture to the negative electrode in a wet state, for example, by using a die coating method or a gravure coating method. The negative electrode to which the mixture has been applied may be further processed, such as by pressing. The form of the separator for the lead-acid battery can be determined so as to be compatible with each component of the lead-acid battery. The positive electrode grid constituting the positive electrode may be lead or a lead alloy, and the positive electrode active material may be lead oxide, such as lead dioxide. The negative electrode grid constituting the negative electrode may be lead or a lead alloy, and the negative electrode active material may be lead, and the lead negative electrode itself may be, for example, in a spongy form. The positive and negative electrode active materials may contain 30% by mass or less of other metal elements in the above composition. The electrolyte may further contain an additive as a source of metal ions such as aluminum ions, lithium ions, and sodium ions.

[0047] By using a separator having the layer of the present disclosure in a lead-acid battery, sulfate ions can easily diffuse in the layer during charging and suppress the increase in concentration, which promotes the charging reaction from the viewpoint of chemical equilibrium and improves the initial charge acceptance. For this reason, it is preferable to dispose the separator of the present disclosure between the positive electrode and the negative electrode of the lead-acid battery. Although not particularly limited, it is preferable to dispose the layer of the separator on the negative electrode side from the viewpoint of improving the charge acceptance of the negative electrode. The separator for lead-acid batteries of the present disclosure can be used in both open-type lead-acid batteries and valve-regulated lead-acid batteries. EXAMPLES

[0048] Examples of the present disclosure will be described in detail below, but the scope of the present disclosure is not limited to the following examples.

[0049] <Content of water-soluble organic solvent> To measure the content of water-soluble organic solvent in the separator (hereinafter referred to as solvent content or simply content), Agilent 6890 manufactured by Agilent Technologies and JEOL Automass SUN manufactured by JEOL Ltd. were used as GC / MS devices, and DB-1 (0.25 mm id x 30 m) liquid layer thickness 25 μm manufactured by Agilent Technologies was used as a column. A lead-acid battery separator sample was shredded, and about 0.3 g was immersed in 2 ml of chloroform for 20 hours, and this extract was directly subjected to GC / MS measurement. The measurement conditions were as follows. [Measurement conditions] Column temperature: 40°C (5 min hold) → (20°C / min heating) → 320°C (11 min hold) Inlet: 320℃ split 1 / 50 Interface: 300℃ Ion source: EI (electron ionization method) Temperature: 240℃ PM: 380V Measurement method: Scan method (ScanRange; m / z 20~800) Injection volume: 1μL As standard samples, chloroform solutions of water-soluble organic solvents of known concentrations were prepared, and measurements were performed under the same conditions as for the samples to create a calibration curve. The amount of water-soluble organic solvent in the samples was quantified from the resulting calibration curve, and this was taken as the solvent content (mass%).

[0050] 《Electrical resistance (ER) of separator in electrolyte》 Ion permeability was evaluated using a Caltronics Palico measurement system, with dilute sulfuric acid with a specific gravity of 1.28 used as the sulfuric acid bath, and the ER of the substrate and separator was calculated under conditions of a sulfuric acid bath temperature of 27°C. Prior to measurement, the substrate and separator were each immersed in dilute sulfuric acid with a specific gravity of 1.28 and a temperature of 27°C for 24 hours. Under the above measurement conditions, the ER of the separator was measured at three points and the average value was calculated. The unit is Ω cm. 2 The ER thus calculated is expressed as the ER ratio, which is the number of times that of the substrate. An ER ratio higher than 1.0 indicates a higher ionic resistance of the membrane.

[0051] The samples of the examples and comparative examples are described in detail below. Example 1 A polyethylene separator (manufactured by Daramic) was used as the substrate. A slurry was prepared to form a laminate. Carbon black (furnace black) having a median particle size of about 1 μm as a solid content, an ionic surfactant, an acrylic copolymer latex, and a thickener (carboxymethylcellulose (CMC)) were dispersed and mixed in an aqueous solvent to prepare a slurry. The aqueous solvent was a mixed solvent of 99% by mass of water and 1% by mass of a water-soluble organic solvent A. A was 2-propanol. The ionic surfactant was 30 parts by mass relative to 100 parts by mass of carbon black in the slurry. The acrylic copolymer latex was 20 parts by mass relative to 100 parts by mass of carbon black in the slurry. The thickener was 10 parts by mass relative to 100 parts by mass of carbon black in the slurry. The slurry was manually applied (hand coated) to the back web-bearing surface of the substrate using an applicator, and dried in an oven at 80° C. for 5 minutes to obtain a separator equipped with a laminate. At this time, the applicator gap (clearance formed between the separator and the applicator) was 45 μm. The solvent content and ER were measured using the obtained separator, and the results evaluated according to the above-mentioned method are shown in Table 1.

[0052] <<Example without water-soluble organic solvent>> As a control example (reference point) for comparing the effect of containing a water-soluble organic solvent, a sample was prepared without using any water-soluble organic solvent at all. The same procedure as in Example 1 was carried out, except that the aqueous solvent used in Example 1 was changed to 100% by mass of water.

[0053] Examples 2 to 18 The same procedure as in Example 1 was carried out, except that 2-propanol (A), the water-soluble organic solvent used in Example 1, was changed to a total of 12 different water-soluble organic solvents as shown below. Example 2: Tetrahydrofuran (B) Examples 3 and 4: Butyl acetate (C) Examples 5 and 6: Methyl ethyl ketone (D) Examples 7, 8, 9, 10: Ethylene glycol monomethyl ether (E) Example 11: Ethyl methyl carbonate (F) Example 12: Phenol (G) Example 13: Acetonitrile (H) Example 14: N,N-Dimethylformamide (I) Example 15: Acetic acid (J) Example 16: Propylene glycol (L) Example 17: Diethylene glycol diethyl ether (M) Example 18: γ-Butyrolactone (O)

[0054] Comparative Examples 1 and 2 The same procedure as in Example 1 was carried out, except that drying for 5 minutes in an oven at 50° C. was carried out instead of drying for 5 minutes in an oven at 80° C. as in Example 1.

[0055] Comparative Examples 3 to 16 The same procedure as in Example 1 was repeated, except that 2-propanol (A), the water-soluble organic solvent used in Example 1, was changed to a total of 11 different water-soluble organic solvents as shown below, and drying for 5 minutes in an oven at 80°C as in Example 1 was changed to drying for 5 minutes in an oven at 50°C. Comparative Examples 3 and 4: Tetrahydrofuran (B) Comparative Examples 5 and 6: Butyl acetate (C) Comparative Example 7: Methyl ethyl ketone (D) Comparative Example 8: Ethylene glycol monomethyl ether (E) Comparative Examples 9 and 10: Ethyl methyl carbonate (F) Comparative Example 11: Phenol (G) Comparative Example 12: Acetonitrile (H) Comparative Example 13: N,N-Dimethylformamide (I) Comparative Example 14: Acetic Acid (J) Comparative Example 15: N-methyl-2-pyrrolidone (K) Comparative Example 16: Propylene carbonate (N)

[0056] The combinations of the examples and comparative examples and the corresponding water-soluble organic solvents are shown in Tables 1 and 2. The boiling points and vapor pressures at 20° C. of the water-soluble organic solvents are shown in Table 3.

[0057] Results of Examples and Comparative Examples Below, Table 1 shows the results of the examples, and Table 2 shows the results of the comparative examples.

[0058] [Table 1-1]

[0059] [Table 1-2]

[0060] [Table 2-1]

[0061] [Table 2-2]

[0062] [Table 3]

[0063] The ER ratio values ​​in the example without a water-soluble organic solvent were 1.13, 1.14, and 1.13, with an average value of 1.13. Comparing the ER ratios of the examples and comparative examples with the example without a water-soluble organic solvent (1.13), when the solvent content of the separator is 0.3% or less, the ER ratio value is lower than 1.13, and the ion permeability is good. Without being bound by theory, it is believed that the presence of a trace amount of water-soluble organic solvent on the microporous surface of the separator introduces an appropriate amount of hydrophilic functional groups, facilitating the movement of ions such as sulfate ions and protons via water molecules.

[0064] On the other hand, when the solvent content of the separator exceeds 0.3%, the ER ratio value is higher than that of the example without water-soluble organic solvent (1.13), and the ion permeability deteriorates. Without being bound by theory, it is believed that the presence of an excess of water-soluble organic solvent on the microporous surface of the separator causes electrical repulsion between the water-soluble organic solvent and sulfate ions and protons, inhibiting the movement of ions. From these results, as shown in Figure 1, it can be seen that when the residual solvent content of the separator is greater than 0 mass% and equal to or less than 0.3 mass%, the ion permeability of the separator is better than when no water-soluble organic solvent is used. [Industrial Applicability]

[0065] The lead acid battery separator of the present invention is useful for lead acid batteries, such as flooded batteries (FB), and is particularly suitable as a separator for enhanced flooded batteries (EFB).

Claims

1. A separator for a lead-acid battery comprising a substrate and a laminate provided on at least one surface of the substrate, the laminate including an inorganic material, and a water-soluble organic solvent contained in the laminate and the substrate, A separator for a lead-acid battery, wherein the content of the water-soluble organic solvent is greater than 0 mass % and not more than 0.3 mass % based on the total mass of the separator for a lead-acid battery.

2. 2. The separator for a lead-acid battery according to claim 1, wherein the water-soluble organic solvent has a boiling point of 200° C. or lower.

3. 3. The lead-acid battery separator according to claim 1, wherein the water-soluble organic solvent has a vapor pressure of 0.04 kPa or more at 20°C.

4. 3. The separator for a lead-acid battery according to claim 1, wherein the inorganic material is a carbon material.

5. 5. The lead acid battery separator of claim 4, wherein the carbon material comprises furnace black, acetylene black, ketjen black, or a combination thereof.

6. A lead-acid battery comprising a battery case, a positive electrode, a negative electrode, and dilute sulfuric acid, the lead-acid battery separator according to claim 1 or 2 being disposed between the positive electrode and the negative electrode.

7. 7. The lead acid battery of claim 6, wherein the laminate is disposed in contact with the negative electrode.

Citation Information

Patent Citations

  • Improved lead-acid battery separators, electrodes, batteries, and methods of manufacture and use thereof

    WO2015171595A1